Revision of Limnocoris Stål (Heteroptera: Nepomorpha: Naucoridae) of the Guiana Shield and Amazon regions - Rodrigues, Higor D. D.; Sites, Robert W. (Zootaxa, 2023)
The species of Limnocoris of the Guiana Shield and Amazon regions of South America are revised, including the descriptions of five new species: L. amazonensis n. sp., L. moreirai n. sp., and L. yanomami n. sp. from Brazil, L. flavescens n. sp. from Venezuela, and L. inflatus n. sp. from Suriname. Further, supplemental descriptions are provided for four previously described species: L. burmeisteri De Carlo, L. fittkaui De Carlo, L. menkei La Rivers, and L. surinamensis Nieser n. stat.; the latter was a subspecies and is here elevated to full species status. The following synonymies are proposed, with junior synonyms in brackets: L. burmeisteri De Carlo [L. lautereri Nieser, Chen & Melo n. syn.] and L. menkei La Rivers [L. birabeni De Carlo n. syn., L. bruchi De Carlo n. syn.]. An illustrated taxonomic key and distribution maps are also presented.